1996
DOI: 10.1084/jem.184.3.1045
|View full text |Cite
|
Sign up to set email alerts
|

Role of the glycocalyx in regulating access of microparticles to apical plasma membranes of intestinal epithelial cells: implications for microbial attachment and oral vaccine targeting.

Abstract: SummaryTransepithelial transport of antigens and pathogens across the epithehal barrier by M cells may be a prerequisite for induction ofmucosal immunity in the intestine. Efficient transport of antigens and pathogens requires adherence to M cell apical surfaces. Couphng of antigen-containing particles to the pentameric binding subunit of cholera toxin (CTB) has been proposed as a means for increasing antigen uptake because the CTB receptor, ganglioside GM1, is a glycohpid present in apical membranes of all in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
229
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(235 citation statements)
references
References 52 publications
4
229
1
1
Order By: Relevance
“…However, survivin recombinant protein (BIRC5) at the same concentrations was not endocytosed (Figure 6). Transferrin (Sandvig and van Deurs, 1990) and CTB (Gizurarson et al, 1992;Frey et al, 1996; , MCF-7, Panc1, PC3, SaOS2, U2OS, HCC, and HBMS cells were cultured with control-or Surv-WT-conditioned medium for 24 h. Cells were fixed and stained with antibodies to HA, magnification  1000. (B) Western blot analysis using antibodies to survivin shows the retarded B18 kDa band of the Flag-HA-survivin fusion protein only in those lysates from the cells grown in conditioned medium.…”
Section: Recombinant Survivin Protein Lacks the Function Of Survivin-mentioning
confidence: 99%
“…However, survivin recombinant protein (BIRC5) at the same concentrations was not endocytosed (Figure 6). Transferrin (Sandvig and van Deurs, 1990) and CTB (Gizurarson et al, 1992;Frey et al, 1996; , MCF-7, Panc1, PC3, SaOS2, U2OS, HCC, and HBMS cells were cultured with control-or Surv-WT-conditioned medium for 24 h. Cells were fixed and stained with antibodies to HA, magnification  1000. (B) Western blot analysis using antibodies to survivin shows the retarded B18 kDa band of the Flag-HA-survivin fusion protein only in those lysates from the cells grown in conditioned medium.…”
Section: Recombinant Survivin Protein Lacks the Function Of Survivin-mentioning
confidence: 99%
“…Furthermore, Western blot analysis under nonreducing conditions revealed that CTB expressed in rice formed a pentamer with 55 to 65 kDa (Fig. 1F), indicating that most of the CTB expressed in rice seed is considered to be a functionally native form possessing the ability to bind to the GM1 ganglioside, known to be expressed at the apical surface of the intestinal epithelium and to be a receptor for CTB (28).…”
Section: Development Of Rice-based Mucosal Vaccine Expressing Choleramentioning
confidence: 99%
“…He suggests that not only do intestinal bacteria stimulate lymphoid elements, but they also influence components of the single layer of epithelium that makes up the mucosal barrier by stimulating the development of microvilli (19,20) and tight junctions (21). These bacteria also activate the release of mucin from epithelial goblet cells to form the glycocalyx as a physical and antibacterial barrier (19)(20)(21)(22). In addition, he provides evidence that intestinal bacteria can stimulate epithelial cells and Paneth cells to release antibacterial peptides into the glycocalyx and lumen which helps to regulate the composition of colonizing intestinal bacteria (19,23).…”
Section: Reviewmentioning
confidence: 99%